Pengaruh Live Streaming, Online Customer Review, Dan Online Customer Rating Terhadap Keputusan Pembelian (Studi Pada Pengguna Marketplace Shopee Di Kecamatan Lowokwaru Kota Malang) - Aulia, Nurul; Rachma, N; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2025)
Abstrack The purpose of this study is to analyze the effect of live streaming, online customer reviews, and online customer ratings on purchasing decisions on the Shopee marketplace targeting Shopee users in Lowokwaru District, Malang City. This study uses a quantitative approach using a questionnaire data collection technique involving 85 respondents. In this study, the sample determination used the Non-probability sampling method, then the sampling technique in this study was the purposive sampling method and data testing using SPSS 25 software. The independent variables in this study are live streaming, online customer reviews and online customer ratings, and the dependent variable is purchasing decisions. The results showed that live streaming has a positive and significant effect on purchasing decisions. In addition, online customer reviews have a positive and significant effect on purchasing decisions, and online customer ratings have a positive and significant effect on purchasing decisions. These three variables together influence purchasing decisions.This research emphasizes the importance of the role of live streaming, online customer reviews, and online customer ratings in increasing consumer trust and strengthening purchase decisions. These results provide implications for developing more effective marketing strategies. Keywords: live streaming, online customerreviews, online customer ratings, purchase decisions, Shopee.